CLIMATE CHANGE AND DIGITAL CONSUMPTIVE BEHAVIOUR ON HOUSEHOLD FOOD SECURITY: AN ANALYSIS OF MAQASHID AL-SHARIAH - Helmi Al Djufri Helmi; Yasfika Ely Nur Afifah (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
Climate change and digital technology development are two factors that have a very complex impact on household food security in Indonesia. Shifts in weather patterns and rising global temperatures not only disrupt food production, but can also affect price stability and people's access to safe and nutritious food. The theoretical study used in this research refers to Ibn Khaldun's thoughts on the relationship between climate, social behaviour, and economic dynamics, as well as modern consumption behaviour theory, which explains how digital technology shapes people's preferences and spending patterns. This study uses a qualitative approach based on a systematic literature review through a process of selecting, classifying, and synthesising relevant literature from books, scientific articles, and other academic sources. The conclusion of this study shows that climate change greatly affects the decline in food productivity and increases supply volatility, while digital consumptive behaviour weakens family financial management due to increased impulsive purchases that change food budget priorities. Digital consumptive behaviour, triggered by ease of access and intensive promotion, diverts the family budget from basic food needs, so that from the perspective of Maqashid Sharia, this violates the principles of benefit, moderation, and reduces the fulfilment of hifz al-māl, hifz al-nafs, and hifz al-nasl. The link between climate change and digital consumption patterns strengthens the vulnerability of household food security, thus requiring the strengthening of literacy, Sharia Maqashid-based financial management, and adaptive strategies to maintain the sustainability of basic needs fulfillment.